Answer: a = 3 Step-by-step explanation: (a, -1) is (x, y) Plug in the value of y into the given equation to solve for a (x): 4x – 3(-1) = 15 4x + 3 = 15 4x = 12 x = 3 (x, y) is (a, -1) so (a, -1) = (3, -1) Log in to Reply

Answer: a=3 Step-by-step explanation: We are given a point and an equation. To see what “a” is, we can plug in the coordinate into the equation and solve for x. 4a-3(-1)=15 [multiply] 4a+3=15 [subtract both sides by 3] 4a=12 [divide both sides by 4] a=3 Now, we know that a=3. Log in to Reply

Answer:a = 3

Step-by-step explanation:(a, -1) is (x, y)

Plug in the value of y into the given equation to solve for a (x):

4x – 3(-1) = 15

4x + 3 = 15

4x = 12

x = 3

(x, y) is (a, -1) so (a, -1) = (3, -1)

Answer: a=3Step-by-step explanation:We are given a point and an equation. To see what “a” is, we can plug in the coordinate into the equation and solve for x.

4a-3(-1)=15[multiply]4a+3=15[subtract both sides by 3]4a=12[divide both sides by 4]a=3Now, we know that

a=3.